Methodological approaches to the research of Bohemianisms in Slavic languages - Hanna Aleksiayevich (Opera slavica, 2023)
The article is devoted to the methodology of detecting and studying Bohemianisms in Slavic languages in the 14th–16th centuries. Several criteria can be used for the study of Bohemianisms: geographical, chronological, philological-textual, formal, semantic and cultural-historical. Each of these criteria makes it possible to address the question of the origin and routes of penetration of Czech words into other Slavic languages only partially. More reliable results of the research can be ensured by a comprehensive use of the given criteria. The theoretical assumptions are supported by examples from Polish, Slovak, Upper and Lower Lusatian, Belarusian, Ukrainian and Russian of the 14th–16th centuries.